Sosialisasi Manfaat Proses Daur Ulang Sampah Plastik di SMA Negeri 2 Darul Makmur - Teuku Farizal; Dian Febrianti; Rita Hartati; Meylis Safriani; Al Munawir; Yasrizal Yasrizal (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2023)
In a broad sense, the management of plastic waste can be approached through the implementation of the 3R framework, which encompasses the principles of Reuse, Reduce, and Recycle. In this endeavor, a process of socialization was undertaken with students from SMA Negeri 2 Darul Makmur pertaining to the issue of waste management, specifically focusing on the potential for recycling and reusing waste materials to generate substantial value. The utilization of waste is facilitated through the implementation of the 3R concept, thereby offering enhanced educational opportunities for participating students. Students will gain a deeper understanding of the recycling process for high-value waste, which is integral to effective waste management. Additionally, they will have the opportunity to witness firsthand the tangible outcomes of transforming plastic waste into liquid fuels. The engagement of students from SMA Negeri 2 Darul Makmur in socialization activities pertaining to the utilization of plastic waste has facilitated a deeper comprehension of waste management processes and the advantages associated with such endeavors. Conversely, students have the potential to utilize plastic waste for practical purposes that are deemed essential in their daily lives.